Standardization of the questionnaire "Personal resource as a predictor of normative behavior of adolescents" - Sunnatova, R.I.; Krushelnitskaya, O.B.; Lanshchikov, D.N. (Psihologo-pedagogičeskie issledovaniâ, 2025)
Context and relevance. A promising approach to solving research and practical problems of preventing deviant behavior in adolescents is the possibility of identifying a personal resource as a condition for preventing behavioral disorders in schoolchildren. A personal resource is understood as a set of personal characteristics of a teenager in combination with the experience of satisfaction with the attitude of significant people towards him/her in the process of interpersonal interaction. Two goals are set: to identify and study the relationship between the personal resource of adolescents and such forms of deviant behavior as tendencies to problematic use of digital gadgets, to suicidal experiences and to violation of school norms and rules; to present the standardization of the created author's questionnaire "Personal resource as a predictor of normative behavior of adolescents". Research hypothesis consisted in the assumption that the personal resource of adolescents, including self-confidence, self-management, satisfaction with the attitude of parents, teachers and classmates, can be considered as a predictor of normative behavior. Methods and materials. The study involved 8-11 grade students (1092 adolescents aged 13-18 (M = 15,82; SD = 1,26)) from five comprehensive Moscow schools. The research methods were: M. Davis's Interpersonal Reactivity Index, D. Campbell's Friendliness Diagnostics, Cook-Medley's Hostility Scale, M. Rokeach's Value Orientations Survey, and the author's the questionnaire "Personal resource as a predictor of normative behavior of adolescents" (R.I. Sunnatova). Results. Statistically significant negative relationships were found between indicators of adolescents' non-normative behavior and self-confidence, self-management, and satisfaction with the attitude of significant others. Regression analysis showed that 25% of the risk of problematic use of digital devices, 30% of the risk of a tendency to violate norms and rules, and 65% of the risk of a tendency to suicidal experiences among adolescents are due to dissatisfaction with the attitude of significant people, as well as indicators of self-confidence, self-management, and responsibility. Conclusions. It has been shown that satisfaction with the attitude of significant adults and classmates is of decisive importance for the normativity of adolescent behavior. The inclusion of teachers and parents in the activities of the psychological service of the school of education, as a form of work, will contribute to the constructiveness of the interaction "adult - teenager", which contributes to the normative behavior of schoolchildren. Контекст и актуальность. Перспективным подходом в решении исследовательских и практических задач профилактики ненормативного поведения подростков представляется возможность выявления личностного ресурса как условия предупреждения нарушений в поведении школьников. Под личностным ресурсом понимается совокупность личностных характеристик подростка в сочетании с переживанием удовлетворенности отношением к нему значимых людей в процессе межличностного взаимодействия. Поставлены две цели: выявить и изучить взаимосвязи личностного ресурса подростков с такими формами ненормативного поведения, как склонности к проблемному использованию цифровых гаджетов, к переживаниям суицидального характера и к нарушению норм и правил школы; представить стандартизацию создаваемой авторской методики «Личностный ресурс как предиктор нормативного поведения подростков». Гипотеза исследования заключалась в предположении о том, что личностный ресурс подростков, включающий веру в себя, самоуправление, удовлетворенность отношением родителей, учителей и одноклассников, может рассматриваться как предиктор нормативного поведения. Методы и материалы. В исследовании приняли участие обучающиеся 8-11 классов (1092 подростка в возрасте 13-18 лет (M = 15,82, SD = 1,26)) пяти общеобразовательных московских школ. Методические средства исследования: «Индекс межличностной реактивности» М. Дэвиса, «Диагностика доброжелательности» Д. Кэмпбелла, «Шкала враждебности» Кука-Медлей, методика «Изучение ценностных ориентаций» М. Рокича и авторская методика «Личностный ресурс как предиктор нормативного поведения подростков» (Р.И. Суннатова). Результаты. Выявлены статистически значимые отрицательные связи показателей ненормативных форм поведения подростков с такими характеристиками, как вера в себя, самоуправление, удовлетворенность отношением значимых людей. Регрессионный анализ показал, что 25% риска возникновения проблемного использования цифровых устройств, 26,1% риска склонности к нарушению норм и правил и 66,2% риска склонности к переживаниям суицидального характера среди подростков обусловлены неудовлетворенностью отношением значимых людей, а также показателями веры в себя, способности к самоуправлению и ответственности. Выводы. Показано, что удовлетворенность отношением значимых взрослых и одноклассников имеет предопределяющее значение для нормативности поведения подростков. Включение в деятельность психологической службы школы просвещения педагогов и родителей как формы работы будет способствовать конструктивности взаимодействия «взрослый - подросток», что способствует нормативности поведения школьников.